Impact of the COVID-19 pandemic on right-wing extremism - Djoric, Marija (Sociološki pregled, 2024)
This paper researches the impact of the COVID-19 pandemic on the security segment of the society, with a special emphasis on right-wing extremism. The author’s main goal is to research the modalities in which the pandemic impacted the extreme right-wing in Serbia and worldwide. On the basis of this comparative analysis, the author will provide an assessment of the similarities and differences between the domestic and foreign right-wing scene, as well as present new trends in this field. A special part of the paper will be dedicated to online recruitment and novelties used by these extremists for radicalization of new members. Apart from the previously known impact of WPM (White Power Music), it is noticeable that fight clubs and online propaganda have a prominent role in recruitment of new members. Given that the pandemic caused a forced physical distancing among people, the work of extremists intensified online, within which an extremely large role of Telegram app was detected. Due to encryption of messages, Telegram is quite interesting not only to right-wing, but to all other extremists as well. A crucial role in the spread of right-wing propaganda was especially given to blogs, such as 4chan, 8chan, 8kun, ShitChan, NeinChan, which are specific due to the fact that they are mostly used by extreme right-wing, given that they do not forbid hate speech. The conclusion is that the value system of the extreme right-wing has remained the same, but the action, as well as the recruitment methods, are indeed changing.